Service Quality and Customer Satisfaction Have an Impact on Increasing Hotel Room Occupancy Ratio: Literature Review Study - Candra, Primadi; Mahaputra, M. Rizky; Mahaputra, M. Ridho (Greenation International Journal of Tourism and Management, 2023)
The aim of this study is to provide qualitative evidence related to the variables of this study from sources derived from national and international indexed journals or scientific articles found through Google Scholar. Researchers then make recommendations from their own perspectives. The research method used in this qualitative study uses a mini-review approach to achieve the research objectives. A mini-evaluation of the variables is done by reading and analyzing dozens of peer-reviewed journal articles. Research results, although still minimal and far from perfect, meet expectations and at least contribute to science and knowledge, especially in the areas of marketing management, service quality variables, customer satisfaction, and revenue improvement. I found out that there is. Just as customer satisfaction variables affect hotel room occupancy, service quality also affects hotel room occupancy. Increasing the above variables should always be done within the study population, especially for guests staying directly at the hotel. It should also be done in future research. There are gaps in other variables that could be used for future research, such as price, advertising, location, loyalty and brand image variables.